Expression analysis of genes located within the common deleted region of del(20q) in patients with myelodysplastic syndromes. (September 2019) - Shiseki, Masayuki; Ishii, Mayuko; Okada, Michiko; Ohwashi, Mari; Wang, Yan-Hua; Osanai, Satoko; Yoshinaga, Kentaro; Mori, Naoki; Motoji, Toshiko; Tanaka, Junji
Highlights: Among 26 genes examined, expression of 8 genes was reduced in patients with del(20q). Expression of 3 genes was reduced in patients without del(20q). Reduced BCAS4 expression could be a prognostic marker for MDS. Abstract: Deletion of the long arm of chromosome 20 (del(20q)) is observed in 5–10% of patients with myelodysplastic syndromes (MDS). We examined the expression of 28 genes within the common deleted region (CDR) of del(20q), which we previously determined by a CGH array using clinical samples, in 48 MDS patients with (n = 28) or without (n = 20) chromosome 20 abnormalities and control subjects (n = 10). The expression level of 8 of 28 genes was significantly reduced in MDS patients with chromosome 20 abnormalities compared to that of control subjects. In addition, the expression of BCAS4, ADA, and YWHAB genes was significantly reduced in MDS patients without chromosome 20 abnormalities, which suggests that these three genes were commonly involved in the molecular pathogenesis of MDS. To evaluate the clinical significance, we analyzed the impact of the expression level of each gene on overall survival (OS). According to the Cox proportional hazard model, multivariate analysis indicated that reduced BCAS4 expression was associated with inferior OS, but the difference was not significant (HR, 3.77; 95% CI, 0.995-17.17; P = 0.0509). Functional analyses are needed to understand the biological significance of reduced expression of these genes in the pathogenesis of MDS.